HOW SINGLE-MEMBER COMPANY IN INDONESIA SHOULD BE REGULATED? (MIXING GIERKE’S THEORY AND ISLAMIC LAW PERSPECTIVE ON LEGAL ENTITY) - Dinda Silviana Putri (Universitas Islam Negeri Mataram, 2022)
The purpose of this study is to evaluate and provide improvements to the regulations governing single-member limited liability companies in Indonesia, related to issues of supervision and restriction using Gierke’s theory and Islamic law perspective on legal entity. This research is structured as a normative legal research using concept, legislation, and comparative approach. The results of the study indicate that there are still shortcomings in terms of supervision and requirements for the establishment of SMLLC in Indonesia both from Gierke’s theory and Islamic law perspective. Thus, the improvements to reporting provisions, the obligation to record all decisions in the minutes, the restrictions on establishment, and the founder requirements are needed.